Conflicts between indigenous and scientific concepts of landscape management for wildlife conservation: human-chimpanzee politics of coexistence at Bossou, Guinea - Gen Yamakoshi; Vincent Leblan (Revue de Primatologie)
Environmental conservation policies in Africa have their origin in the forced establishment of nature reserves during the colonial era. Even after African countries became independent, top-down operation of these reserves continued primarily due to international calls for nature conservation and to consumerist demand from western countries. For the people of Africa, this continued to be an externally-driven activity with little endogenous motivation and, quite often, real motives for opposition. Even in the context of today’s participatory conservation approaches, there is vocal skepticism about the ability of Africans to act independently and about the existence of local “conservation” philosophies. This paper offers a detailed description of field clearing demonstrations by the villagers of Bossou, Republic of Guinea, which flared up in 2002 following the establishment of a governmental research institute in the village. This place had been portrayed for several decades by natural scientists as a place of peaceful coexistence between people and chimpanzees. The stated goals of the swidden preparation campaign was to secure land for subsistence purposes, but it is thought that the main driving factor was maintaining the right to decide matters like the allocation of tourism income, which the government research institute was attempting to usurp. After the general 2002 uprising, a particular individual and his family continued their resistance consisting of swidden preparation and cultivation in the chimpanzee habitat. This was likely due to a conviction to recover the original vegetative landscape of the village, which had been transformed under the pressure of academic research, to its prior state. The agricultural environment is valued by a chimpanzee “conservation model” based on indigenous experience and knowledge, which is in conflict with models introduced by outsiders (scientists and public administrations).The indigenous conservation model revealed by this case study may better help to prevent epidemics of zoonoses and injury and deaths due to chimpanzee attacks, compared with the outsiders’ conservation approach based on general knowledge drawn from conservation ecology. Future conservation measures should be determined based on dialog between the two models. This article is modified after Yamakoshi (2006a).